1976
DOI: 10.1104/pp.57.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Helminthosporium maydis, Race T, Toxin on Potassium Uptake in Maize Roots

Abstract: The effect of a toxin extract of Helminthosporium maydis, race T on K + (86Rb) uptake by excised root segments of normal (N) and Texas cytoplasmic male-sterile (T) versions of corn inbred W64A was investigated. The uptake of K+ was inhibited in both N and T roots by the toxin. This was true for both basal (freshly excised) and augmented (pretreated with aeration) K+ uptake. Augmented uptake was more toxin-sensitive than basal uptake (irrespective of cytoplasm type), and the augmented uptake in T roots was seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1977
1977
1979
1979

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In the present study, washing corn root segments in aerated K-phosphate and CaCl2 solutions increased the rate of K+ (wRb) uptake by 5-fold with little or no lag and the rate leveled off after 4 h. In contrast, washing increased phosphate uptake by only 2-to 3-fold during the same 4-h period with an initial lag of 30 to 40 min. These results agree well with previous studies on the stimulation of ion uptake by washing (5,13,16,19 …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, washing corn root segments in aerated K-phosphate and CaCl2 solutions increased the rate of K+ (wRb) uptake by 5-fold with little or no lag and the rate leveled off after 4 h. In contrast, washing increased phosphate uptake by only 2-to 3-fold during the same 4-h period with an initial lag of 30 to 40 min. These results agree well with previous studies on the stimulation of ion uptake by washing (5,13,16,19 …”
Section: Resultssupporting
confidence: 83%
“…Previous studies with excised corn root segments have shown that washing immediately increased K+ uptake activity (5,19) and membrane potential (15) with uptake increasing by 3-to 7-fold and the membrane potential increasing to a maximum of 25 mv within 4 h. In contrast to K+, Pi uptake (13,16) increases only 2-3-fold after a 30-min lag period. Based on these washing response data and the study of the effect of dithioerythritol on membrane potential, resistance, and proton fluxes (17), Hanson and Lin (7,17) suggested that active salt transport and its regulation arise from the functioning of a proton-extruding, cation-carrying ATPase in the membrane, balanced by H+/cation and OH-/anion antiporters.…”
mentioning
confidence: 95%
“…rates increase with increasing distance from the apex through 6 cm from the apex (4). Basal K+ uptake in T versions is more toxin-sensitive than in N versions only in the apical root region of inbred W64A; in more mature regions (cm segments 2 + 3 + 4 from the apex), basal uptake is equally toxin-sensitive in N and T. Augmented K+ uptake in these more mature regions of N and T roots is more toxin-sensitive than basal K+ uptake, and the augmented increment in K+ uptake rate is inhibited 20 to 25% by toxin in N and 70 to 80% in T. Thus, despite the likelihood that the mechanism of K+ uptake is in all cases the same, differences exist in toxin sensitivity of K+ uptake between basal and augmented rates for the same root region, N and T versions for the same root region, and apex and midzone regions of the same root (4).…”
mentioning
confidence: 96%
“…With the exception of the leaf chlorosis bioassay (3,9,11,15), the effects of the toxin(s) of H. maydis, race T, are not restricted to T cytoplasm. Thus, a qualitative distinction between plants with N and T cytoplasms is rarely observed since N plants are sensitive at high toxin concentrations (4,6,11,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation